Metatarsal Salmonella enteritidis osteomyelitis in a healthy child - Limão, S (2019)
Non-typhoidal Salmonella osteomyelitis in healthy children is a very rare condition. A previously healthy 7-year-old boy presented with foot pain following a small injury. Local inflammatory signs of the foot were observed, with a normal radiograph. Two weeks before, he had had gastroenteritis. Assuming cellulitis, flucloxacillin was began. Early during admission, surgical subcutaneous abscess drainage was performed and Salmonella enteritidis was identified. According to bacterial susceptibility, antibiotherapy was changed to ceftriaxone. A foot radiograph and an MRI scan, performed on the 9th and the 12th days, revealed findings suggestive of osteomyelitis of the metaphysis of the fifth metatarsal. Clinical worsening persisted and surgical extensive debridement was needed. A 6-week antibiotic treatment was completed, with a good outcome. Osteomyelitis with a poor evolution in children with risk factors (prior gastrointestinal illness, warm weather and previous exposure to antibiotics) can raise the possibility of a non-typhoidal Salmonella infection.